Application Of The Non-Destructive Test For FKASA Building Evaluation - Muhammad Afnan Syamim, Abdul Manaf (2023)
The evaluation of concrete quality is important to identify where the concrete needs to do maintained. Non-destructive testing (NDT) has been used more frequently to evaluate the condition of buildings. This evaluation includes a wide range of activities, including a simple visual inspection. During the maintenance stage, buildings are monitored more often. Special efforts have been placed on the complementary application of various NDT techniques into an integrated structural health monitoring (SHM) system. The main objective of the study is to evaluate the condition of the reinforced concrete structure at Universiti Malaysia Pahang Kampus Paya Besar, Gambang. The present study used the non-destructive test (NDT) tools to determine the condition of the FKASA building. Two major types of building structures, namely, beams and columns were selected to assess the building’s quality. Two NDT tests used are rebound hammer (RH) and ultrasonic pulse velocity (UPV). Finally, the results and analysis show that the condition of the beams and columns at the FKASA building is satisfactory and poor. For the strength beams and columns, it was found that the condition for both structure elements was a very good hard layer and fair, respectively.